Public health research priorities in Europe seen by non-governmental organizations - Gulis, Gabriel; Garrido-Herrero, Lara; Katreniakova, Zuzana; Harvey, Gabrielle; McCarthy, Mark; Slovak Public Health Association (Central European journal of public health, 2008)
BACKGROUND: Public health research is concerned with population health, determinants of health, health systems research, health promotion, environmental health, health protection, disease prevention and research in other fields of public health. During the last decades, non-governmental organisations (NGOs) are more often entering the field of public health research. This paper presents results of work within SPHERE (Strengthening Public Health Research in Europe), a European Commission funded study aimed to gather information and produce knowledge on the state of public health research in Europe. METHODS: A questionnaire survey was developed and conducted among NGOs enrolled in a database held by the European Public Health Alliance (EPHA). There were 80 replies, and the response rate for NGOs that were members of EPHA was 53%. RESULTS: There were no significant statistical differences in the responses when analysed for three European groups ['old' member states (EU 15), accession members states in 2004 (EU 10) and EU-associated countries]. The NGOs reported a relatively large international experience, expressed by participation in international public health research, and more often practice work. The main research priorities reported were general public health, environmental health, ADHD, obesity, nutrition, tobacco control. NGOs showed low correlation between their work field and their proposed public health research priorities. CONCLUSION: There are growing numbers of NGOs in Europe concerned with public health. This survey indicates their interest also in public health research priorities.
Keywords: Attention Deficit Disorder with Hyperactivity; Public Opinion; výzkum; Tobacco Use Disorder; mezinárodní agentury; Databases, Factual; Humans; databáze faktografické; Obesity; Europe; Mental Health; environmentální zdraví; Environmental Health; Organizations; Needs Assessment; veřejné mínění; Surveys and Questionnaires; organizace; poruchy vyvolané užíváním tabáku; veřejné zdravotnictví; průzkumy a dotazníky; Evropa; hyperkinetická porucha; odhad potřeb; lidé; duševní zdraví; Public Health; Attitude to Health; International Agencies; Research; postoj ke zdraví; obezita